Perencanaan Pembelajaran Pada Pembelajaran Tatap Muka Terbatas Di Madrasah Ibtidaiyah - Ramdanil Mubarok (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2022)
ABSTRACT A maximum The case of the spread of Covid-19 which is starting to decrease provides a wide range of motion for every educational institution to carry out face-to-face learning, although it is still with a limited face-to-face learning model. The purpose of writing this article is to analyze lesson planning in Madrasah Ibtidaiyah and the importance of lesson planning in Madrasah Ibtidaiyah in limited face-to-face learning. This research is qualitative research with the type of library research (library research). The data analysis is carried out by collecting data, reducing data, presenting data, and drawing conclusions. The result is that limited face-to-face learning plans are prepared through a good understanding of the curriculum, mastery of teaching materials, and preparation of teaching programs. Then proceed with the implementation of teaching programs, assessment of teaching programs, and determining student learning outcomes. Among the important roles of limited face-to-face learning planning include: making learning more systematic, easy to analyze student learning success, delivering material more easily, learning patterns are easy to organize, can save time and effort, and becoming material for evaluation and reflection. The hope is that an understanding of learning planning in Madrasah Ibtidaiyah and the importance of learning planning in Madrasah Ibtidaiyah in limited face-to-face learning can be input for the development of learning in Madrasah Ibtidaiyah in particular and learning in general.